PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 017 BAGAN PUNAK MERANTI - Linda Linda; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research up on its low usufructs student studying Class V SD Negeri 017 Bagan Punak Meranti. Initially, of 24 students which reach KKM just 9 person (37,50 %), with average brazes 60,41. Therefore, this research try Learning Approaching Implement Contextual Teaching And Learning (CTL) to Increase IPS Studying Result Student class V SD Negeri 017 Bagan Punak Meranti. On this research Observational mengunakan Action brazes (PTK) with analisis's tech kualitatif's data. Observational job mechanism action brazes this, rendered in cycle form (plotted 2 cycles), one that each its cycle ranges 4 activities / phases, which is (1 ) plannings (2 ) performings (3 ) watches and (4 ) reflections. Activity result learns on meet i. cycle first which is 68,75% by enough categories, then increasing on appointment second becomes 81,25 % get categories well. On cycle II. appointment first increases 87,50% by good categories, then on appointment second increases again 93,75% by good peer categories. Student activity result on meet i. cycle percentage first 56,25% get reducing categories, then on second appointment 62,50% also get enough categories, on cycle II. first appointment 68,75% get enough categories, on second Cycle appointment II. also experience step-up 87,50 % by ketegori well. On cycles daily dry run i. student which complete 15 students whereas that don't complete 9 students, with klasikal's thoroughness 62,5 % (are not complete). Base it yielding IPS studying experience step-up as big as 15,04% on i. cycle and 36,15% on cycle II. This research gets to be concluded that penerapam CTL learning approaching can increase IPS studying result student class V SD Negeri 017 Bagan Punak Meranti.Key word : Learning approaching Contextual Teaching And Learning (CTL) IPS Learnedresult .